Environmental supplement book of flood disaster for university students - Ilmi Zajuli Ichsan; Agung Purwanto; Henita Rahmayanti (Institute of Advanced Engineering and Science, 2023)
Solving natural disaster problems, especially floods, requires community participation. One of the efforts that can be done is by implementing the environmental supplement book of flood disasters based on innovation learning model for natural science and environmental learning (ILMIZI). The purpose of this research was to implement a supplementary book to improve university students’ higher order thinking skills (HOTS) and pro-environmental behavior (PEB). This was an experiment method consisting of experimental class and control class. The samples were 115 university students with 60 university students in experimental class and 55 university students in control class. The data analysis was a t-test that aims to test the significance of the difference in the mean HOTS and PEB scores for the experimental class and the control class. In addition to the t-test, descriptive analysis was also carried out by comparing the HOTS and PEB scores between the experimental class and the control class. The results of this study indicated that the t-test results were significant, which means that supplement books could increase HOTS and PEB of university students. The results of the descriptive analysis showed that university students were still weak in flood mitigation efforts related to the provision of disaster evacuation tools. In an effort to prevent disasters, it was necessary to innovate environmental learning to support sustainability. A conclusion can be drawn that the use of supplementary books can increase university students’ HOTS and PEB.